2013
DOI: 10.1016/j.colsurfa.2012.11.032
|View full text |Cite
|
Sign up to set email alerts
|

Effects of surface Fe(III) oxides in a steel slag on the formation of humic-like dark-colored polymers by the polycondensation of humic precursors

Abstract: Carbonated furnace steel slag is effective in enhancing polycondensation reactions of humic precursors such as quinones, amino acids and saccharides. To obtain more detailed information concerning the nature of the catalytic sites on the surface of slag, a pristine slag sample was treated with HNO 3 , HF and NH 2 OH to alter the surface states.The catalytic activities for the formation of humic-like dark-colored polymers were significantly decreased for the samples treated with HNO 3 or HF compared to untreate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 39 publications
0
16
1
Order By: Relevance
“…In marine sediment, the transformation of humic substances could have occurred through complex reactions, including bacterial degradation, bacterial synthesis, and abiotic reaction with mineral matter having catalytic properties. 35 Nishimoto et al 15 demonstrated that the catalytic activity of steelmaking slag for the formation of humiclike substances in the autoclaved solution from catechol, glycine, and glucose, which were compared to the observation interval in this study (3 months); thus, we could not detect the intermediate of FL2 in this study. Furthermore, in the catalytic experiment, iron oxide on the surface of the steelmaking slag was reductively eluted.…”
Section: Analytical Sciencescontrasting
confidence: 50%
See 1 more Smart Citation
“…In marine sediment, the transformation of humic substances could have occurred through complex reactions, including bacterial degradation, bacterial synthesis, and abiotic reaction with mineral matter having catalytic properties. 35 Nishimoto et al 15 demonstrated that the catalytic activity of steelmaking slag for the formation of humiclike substances in the autoclaved solution from catechol, glycine, and glucose, which were compared to the observation interval in this study (3 months); thus, we could not detect the intermediate of FL2 in this study. Furthermore, in the catalytic experiment, iron oxide on the surface of the steelmaking slag was reductively eluted.…”
Section: Analytical Sciencescontrasting
confidence: 50%
“…11 It has been reported that terrestrial humic substances were degraded rapidly in the coastal area by marine bacteria 3,12,13 ; however, some researchers have reported that steelmaking slag enhanced polycondensation when it is incubated with low molecular organic compounds. 14,15 There is a limit in the previously reported data to understanding what occurred in HAs when they mixed with steelmaking slag in coastal seawater. 11 Thus, a detailed structural characterization of HAs would be predicted to provide crucial information about the fate of terrestrial HAs with steelmaking slag under coastal seawater.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of side reactions could also occur by electron accepted HA with a neighboring HA, as described by the equations below: 9) HAred + HA HA + HA where HA' represent a structurally altered HA by selfoxidation. These side-reactions could inhibit the reductive Fe elution when the concentration of HA was enlarged.…”
Section: Discussionmentioning
confidence: 99%
“…Low-molecular-weight products such as phenols, phenolic acids, sugars, and amino acids may be formed by the degradation of proteins, polysaccharides, lignins, and polyphenols. Humic substances commonly are considered to be formed via polycondensation of low-molecular-weight products (Haumaier and Zech, 1995;Nishimoto et al, 2013). Zhao et al (2014) sequentially extracted different organic matter fractions by neutral solutions and acid solutions from the original biomass and their derived biochars to tracking the evolution of carbon forms.…”
Section: Introductionmentioning
confidence: 99%